Perbandingan Metode Granulasi Basah dan Kempa Langsung Terhadap Sifat Fisik dan Waktu Hancur Orally Disintegrating Tablets (ODTs) Piroksikam - Wira Noviana Suhery; Armon Fernando; Buddy Giovanni (Jurnal Sains Farmasi & Klinis, 2016)
Study on comparison of wet granulation and direct compression method of physical properties and disintegration time of orally disintegrating tablets piroxicam has been done. This study aims to comparison which method gives better results of physical properties and disintegration time between wet granulation and direct compression method. Both methods are made with the same composition formula of each tablets is Piroxicam 20 mg, Primellose® 5%, 1% PVP K30, magnesium stearate 1%, Mannitol 10%, and Comprecel® up to 175 mg. ODTs then evaluated physical properties which include weight variation, thickness, hardness, friability and friksibility, disintegration time, ratio of water absorption, wetting time, drug content and dissolution test. The results showed that both methods produce the physical properties of a good tablets. However, the method of direct compression provides a disintegrating faster 55.51 seconds compared with the wet granulation method. Statistical test using independent sample T test showed that there were significant differences in the disintegration time (P <0.05) between the formula with the method of direct compression and wet granulation.